Mycobacterium neoaurum line-related bacteremia with pulmonary involvement: Case report and review of literature. (2018) - Walayat, Saqib; Awwal, Talha; Roy, Moni; Ahmad, Sharjeel
Abstract: Mycobacterium neoaurum is a rapidly growing non-tuberculous mycobacterium which is ubiquitous in nature. While it can cause line related infections in immunocompromised host, case reports of urinary tract infections, cutaneous infections, pulmonary infections, and meningoencephalitis have also been reported. We report the first case of Mycobacterium neoaurum line related bacteremia with concomitant pulmonary involvement. Our patient responded well to a nine week course of antimicrobials after removal of infected central line.